Cyber Physical System For Autometed Weather Station And Agriculture Node In Smart Farming - Kurnia Mustika Wati (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The Cyber-Physical System is a key system in the implementation of the 4th generation industrial revolution. This system combines automation systems, electronics, internet networks and machine learning. The implementation of physical cyber systems in agriculture is one of the long-awaited applications because it is the backbone of the implementation of sustainable agribusiness systems. With this system precision agriculture and pervasive computing in agriculture can help stakeholders in agribusiness to enjoy various benefits optimally. One example of its application is a smart farming system that is conditioned to provide measurable and maximum yields without having to sacrifice soil nutrients because it is well monitored according to weather conditions. In previous studies, several LoRa communication-based systems for monitoring local weather in a place and measurements of soil nutrient conditions have been carried out and displayed through the internet network. Monitoring and control systems on other agricultural models based on hydroponics and aquaponics have also been carried out for some types of crops. The results provide greater potential for wider application and in actual conditions in the agricultural industry. In this study, the integration of physical cyber systems with lora communication-based agricultural monitoring and control nodes will be carried out more broadly by considering the local conditions under which the system is tested. In this case, the research will be carried out at the Research and Recreation Park, Telkom University and agrifarming industry partners as a model of actual application. The research findings show that the application of advanced sensor technology has improved the accuracy of weather measurements by up to 95%. Quantitative data collected from the new weather station showed a significant improvement in weather monitoring. Qualitatively, positive responses from stakeholders such as disaster management authorities and farmers were also noted. In conclusion, the development of this modern weather station supports the community's need for reliable weather information and is a step forward in addressing the challenges of climate change.